Environmental impact of storage of lignite and black shale waste rocks at South Jimblebar Iron Ore Mine, Western Australia - Fajrin, Andi Muhammad (Curtin University, 2013)
This study assessed the geochemical characteristics of lignite and other waste rock of the future South Jimblebar Iron Ore Mine in Western Australia. Results indicated that lignite of CzD 2 and black shale of MU stratigraphic units were potentially acid forming (PAF) materials and relatively enriched in certain elements of environmental significance. In contrast, non-carbonaceous mudstones were non-acid forming (NAF). These findings indicate potential for acid mine drainage generation that will requires specific waste rock management.